2017
DOI: 10.1159/000468977
|View full text |Cite
|
Sign up to set email alerts
|

Painful Leg Ulceration in a Poorly Controlled Hypertensive Patient: A Case Report of Martorell Ulcer

Abstract: Martorell ulcer is a form of lower limb ulceration, preceded by a small area of excruciating pain. It often appears as a solitary lesion on the outer aspect of the lower limb, and is primarily associated with poorly controlled hypertension and diabetes. Treatment of the ulcer involves awareness and early correct diagnosis, adequate control of blood pressure, management of infection, and wound care. We describe a 77-year-old diabetic and hypertensive woman presenting with excruciating pain in her right lower la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Chronic wounds, including diabetic foot ulcers, venous leg ulcers and pressure ulcers, do not adhere to the standard time course of cellular and molecular events that lead towards healing of healthy acute wounds. Martorell HYTILU represents rapidly progressive and extremely painful ulcers that are frequently underdiagnosed, being a great clinical, therapeutic and biomedical challenge [1][2][3]14]. The molecular basis of Martorell ulcers is generally unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic wounds, including diabetic foot ulcers, venous leg ulcers and pressure ulcers, do not adhere to the standard time course of cellular and molecular events that lead towards healing of healthy acute wounds. Martorell HYTILU represents rapidly progressive and extremely painful ulcers that are frequently underdiagnosed, being a great clinical, therapeutic and biomedical challenge [1][2][3]14]. The molecular basis of Martorell ulcers is generally unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Martorell HYTILU is extremely painful and slowly healing ulcers characterized by localized subcutaneous arteriosclerosis, occlusion of small vessels, local skin ischemia, and infarction. Though, first described by Martorell, and Hines and Farber in the 1940s, surprisingly little is known about underlying molecular mechanisms of impaired healing of such type of ulcers [3]. There is the scarcity of publications on this issue in Ukraine and no official statistical releases reporting the disease epidemiology.…”
mentioning
confidence: 99%
“…Cases reported by Malhi et al and Lima Pinto et al also demonstrated full wound healing following surgical debridement to the fascia, split-thickness skin grafting, and/or negative-pressure wound therapy. 12,13 For superficial forms of HYTILU, punch split-thickness grafts represent an elegant and technically less demanding solution. Conde Montero et al achieved complete wound healing 4 weeks after 4 and 6 mm punch split-thickness grafting under local anesthesia.…”
Section: Surgical Managementmentioning
confidence: 99%
“…Laboratory results showed anemia (Hb 7.6), hypoalbuminemia (2.7), increased cholesterol level (244.0 mg/dL), high triglyceride (153.0 mg/dL), increased serum urea (170.4 mg/dl), increased serum creatinine (11.23 mg/dl), high calcium (10.4 mg/dl), high inorganic phosphorus (8.5 mg/dl) and high parathyroid hormone (2,164). Radiographic examination revealed cardiomegaly, aortic atherosclerosis, and congestive pulmonum.…”
Section: Casementioning
confidence: 99%
“…1 The most common causes of lower extremity ulcer are venous insufficiency, arterial insufficiency, and neuropathy. 1,2 Ulcers associated with systemic condition often face diagnostic and therapeutic challenge. 1 Other causes of lower extremity ulcers include lymphedema, infection, trauma, vasculitis, calciphylaxis, drug-induced, malignancy, autoimmune disease, and pyoderma gangrenosum.…”
Section: Introductionmentioning
confidence: 99%